Brightly coloured tissues in limid bivalves chemically deter predators. Issue 10 (2nd October 2019) - Dougherty, Lindsey F.; Niebergall, Alexandria K.; Broeckling, Corey D.; Schauer, Kevin L.; Li, Jingchun
Abstract : Members of the marine bivalve family Limidae are known for their bright appearance. In this study, their colourful tissues were examined as a defence mechanism towards predators. We showed that when attacked by the peacock mantis shrimp ( Odontodactylus scyllarus ), the 'disco' clam, Ctenoides ales, opened wide to expose brightly coloured tissues to the predator. The predator also significantly preferred to consume the internal, non-colourful clam tissues than the external, colourful tissues. Mass spectrometry-based metabolomic analysis confirmed that colourful tissues had significantly different chemical compositions than the non-colourful ones. The internal, non-colourful tissues had metabolite profiles more similar to an outgroup bivalve than to the species' own colourful external tissues. A number of the compounds that differentiated the colourful tissues from the non-colourful tissues appeared to be peptide-like, which potentially serve as the underlying defensive compounds. This is the first study demonstrating that colourful bivalve tissues are used for chemical defence.